Research on cross-domain translation method for core and electrical imaging images based on CUT - Yang Chen; Sinan Fang; Hongtao Wu; Hao Ma; Guilan Lin; Manxin Li; Chenxi Xue; Zeyu Zhang (Journal of Applied Geophysics, 2026)

Mechanism of surface-functionalized materials for efficient iodide removal: Performance and theoretical insights - Meng Ren; Xuedan Cui; Sai Yuan; Ying Yang; Xiaotian Xu; Pengjie Zhao; Tianda Pu; Guilan Duan; Yinjie Zhang; Aijun Lin (Journal of Environmental Chemical Engineering, 2026)

Evaluating technical soil derived from lithium mica residue: Integrating soil quality and life cycle assessment for functional performance and environmental sustainability - Yanqi Li; Zi Guo; Xinyan Lv; Xin Liao; Guilan Duan; Liping Fang; Xiaoliang Li; Xiao Tan; Aijun Lin (Journal of Cleaner Production, 2026)

A comprehensive study on coastline mapping and sustainable management of coastal resources in China: Connotation, methodologies, and practical applications - Weiwei Dong; Guilan Lin; Yongling Zheng; Huiquan Lu; Chengqiang Wu; Jingjing Bao (Journal of Coastal Conservation, 2025)

Dynamic snake vision mask r-cnn: a method for microfracture detection in electrical logging imaging - Yihang Lu; Sinan Fang; Yi Yu; Huimin Wu; Guilan Lin; Guohao Ma; Zehan Wang (Earth Science Informatics, 2025)

Long-term effectiveness evaluation of Cr(VI)-contaminated soil remediation with modified iron-biochar composites - Lihong Xie; Yi Zhou; Qiyan Ma; Jinlan Zhang; Guilan Duan; Aijun Lin; Yong Xiao; Tingting Zhang (Journal of Environmental Chemical Engineering, 2025)

The Interplay Between Climate Warming Driven by Greenhouse Gas Emissions and the Ecotoxicological Effects of Microplastics: Insights From a Meta‐Analysis - Xinyan Lv; Aijun Lin; Xuedan Cui; Yanqi Li; Zi Guo; Xiao Tan; Guilan Duan (Global Change Biology, 2025)
An increasing number of studies have revealed the interconnections and interactions between global warming and microplastics. However, research in this field is still in its early stages, with fragmented content and inconsistent conclusions. Therefore, this paper adopts a meta‐analysis method to summarize and analyze the relevant literature in this area. After screening, a total of 39 research papers and 730 data points related to the interactions between global warming and microplastic pollution were obtained. The research results indicate that, on one hand, soil microplastic pollution significantly increases greenhouse gas CO 2 emissions by 140.20%, N 2 O emissions by 195.27%, and Global Warming Potential by 172.10%, thereby exacerbating global warming. By introducing explanatory variables for analysis, it was found that microplastic type, soil type, and soil dissolved organic carbon are important influencing factors. On the other hand, the study also explains that the rise in water temperature due to global warming amplifies the biological toxicity effects of microplastics, leading to oxidative damage and poisoning in aquatic animals. The bidirectional interaction mechanism between microplastic pollution and global warming may form a vicious cycle, further increasing the vulnerability of ecosystems. This study provides a theoretical basis and research direction for addressing the dual threats of microplastic pollution and global warming.

Application of a Dual-Stream Network Collaboratively Based on Wavelet and Spatial-Channel Convolution in the Inpainting of Blank Strips in Marine Electrical Imaging Logging Images: A Case Study in the South China Sea - Guilan Lin; Sinan Fang; Manxin Li; Hongtao Wu; Chenxi Xue; Zeyu Zhang (Journal of Marine Science and Engineering, 2025)
Electrical imaging logging technology precisely characterizes the features of the formation on the borehole wall through high-resolution resistivity images. However, the problem of blank strips caused by the mismatch between the instrument pads and the borehole diameter seriously affects the accuracy of fracture identification and formation continuity interpretation in marine oil and gas reservoirs. Existing inpainting methods struggle to reconstruct complex geological textures while maintaining structural continuity, particularly in balancing low-frequency formation morphology with high-frequency fracture details. To address this issue, this paper proposes an inpainting method using a dual-stream network based on the collaborative optimization of wavelet and spatial-channel convolution. By designing a texture-aware data prior algorithm, a high-quality training dataset with geological rationality is generated. A dual-stream encoder–decoder network architecture is adopted, and the wavelet transform convolution (WTConv) module is utilized to enhance the multi-scale perception ability of the generator, achieving a collaborative analysis of the low-frequency formation structure and high-frequency fracture details. Combined with the spatial channel convolution (SCConv) to enhance the feature fusion module, the cross-modal interaction between texture and structural features is optimized through a dynamic gating mechanism. Furthermore, a multi-objective loss function is introduced to constrain the semantic coherence and visual authenticity of image reconstruction. Experiments show that, in the inpainting indexes for Block X in the South China Sea, the mean absolute error (MAE), structural similarity index (SSIM), and peak signal-to-noise ratio (PSNR) of this method are 6.893, 0.779, and 19.087, respectively, which are significantly better than the improved filtersim, U-Net, and AOT-GAN methods. The correlation degree of the pixel distribution between the inpainted area and the original image reaches 0.921~0.997, verifying the precise matching of the low-frequency morphology and high-frequency details. In the inpainting of electrical imaging logging images across blocks, the applicability of the method is confirmed, effectively solving the interference of blank strips on the interpretation accuracy of marine oil and gas reservoirs. It provides an intelligent inpainting tool with geological interpretability for the electrical imaging logging interpretation of complex reservoirs, and has important engineering value for improving the efficiency of oil and gas exploration and development.

Reduction-stabilization characteristics, long-term stability and biotoxicity evaluation of Fe(II)/Al layered double hydroxides on Cr(VI) in contaminated soil - Xiao Tan; Qi Liu; YanQi Li; Xinyan Lv; Zi Guo; Guilan Duan; Aijun Lin (Environmental Pollution, 2025)

Long-term effectiveness of heavy metal(loid) stabilization: Development of an assessing method - Yanqing Liu; Zewen Wang; Xiao Tan; Deyi Hou; Liping Fang; Aijun Lin; Fangbai Li; Guilan Duan (Environmental Pollution, 2025)

Efficient remediation of different concentrations of Cr-contaminated soils by nano zero-valent iron modified with carboxymethyl cellulose and biochar - Lihong Xie; Qiyan Ma; Qingjun Chen; Yiyang Liu; Pengfei Guo; Jinlan Zhang; Guilan Duan; Aijun Lin; Tingting Zhang; Shangyi Li (Journal of Environmental Sciences, 2025)

Zero-valent iron on graphite-cellulose biochar catalysts for the Fenton degradation of tetracycline from water - Shuai Chen; Yuanchuan Zhao; Guilan Gao; Hao Dong; Feng Yuan; Donghai Lin; Jie Guan; Aleksandra Nesic; Junli Xu; Carolina Belver; Jorge Bedia (Process Safety and Environmental Protection, 2024)

Efficacy and safety of dabigatran and rivaroxaban in atrial fibrillation patients with impaired liver function: a multicenter retrospective cohort study - Xinhai Huang; Wenlin Xu; Guilan Wu; Ruijuan Li; Ping Gu; Qiaowei Zheng; Xiumei Liu; Hengfen Dai; Xiangsheng Lin; Yuxin Liu; Xiaoming Du; Jun Su; et al. (European Journal of Clinical Pharmacology, 2024)

Characteristics of three organic fertilizers and their influence on the mobility of cadmium and arsenic in a soil-rice (Oryza sativa L.) system - Xiao Tan; Jinman Cao; Jiahao Liu; Jinhang Wang; Guilan Duan; Yinjie Zhang; Jun Cui; Aijun Lin (Environmental Science and Pollution Research, 2024)

Effects of remediation agents on rice and soil in toxic metal(loid)s contaminated paddy fields: A global meta-analysis - Meng Liu; Ruiqing Xu; Xuedan Cui; Daibing Hou; Pengjie Zhao; Yanzhao Cheng; Yujie Qi; Guilan Duan; Guodong Fan; Aijun Lin; Xiao Tan; Yong Xiao (Science of The Total Environment, 2024)

Is Cr(III) re-oxidation occurring in Cr-contaminated soils after remediation: Meta-analysis and machine learning prediction - Xiao Tan; Fang Qi; Qi Liu; Hantong Qie; Guilan Duan; Aijun Lin; Meng Liu; Yong Xiao (Journal of Hazardous Materials, 2024)

Effects of artificial sweetener acesulfame on soil-dwelling earthworms (Eisenia fetida) and its gut microbiota - Xianglong Lin; Zhelun Liu; Weiran Wang; Guilan Duan; Yongguan Zhu (Science of The Total Environment, 2024)

Enhanced remediation of Cr(VI)-contaminated soil by modified zero-valent iron with oxalic acid on biochar - Lihong Xie; Qingjun Chen; Yiyang Liu; Qiyan Ma; Jinlan Zhang; Chenliu Tang; Guilan Duan; Aijun Lin; Tingting Zhang; Shangyi Li (Science of The Total Environment, 2023)

Remediation of Cr(VI)-contaminated soil by ball milling modified zero-valent iron biochar composites: Insights into long-term stability and microbial community - Pengfei Guo; Jinlan Zhang; Yi Zhou; Chenliu Tang; Xiaohui Wang; Xiaoping Gao; Guilan Duan; Aijun Lin; Tingting Zhang; Shangyi Li (Journal of Environmental Chemical Engineering, 2023)

Pexidartinib hydrochloride exposure induces developmental toxicity and immunotoxicity in zebrafish embryos via activation of Wnt signaling - Fasheng Liu; Hongmei Hu; Guilan Chen; Yanqi Lin; Wei Li; Ziyi Liu; Chao Chen; Xue Li; Sujie Sun; Li Zhang; Dou Yang; Kangyu Liu; et al. (Fish & Shellfish Immunology, 2023)

Metagenomic insights into the inhibitory mechanisms of Cu on fermentative hydrogen production - Jinman Cao; Guilan Duan; Aijun Lin; Yaoyu Zhou; Siming You; Jonathan W.C. Wong; Guang Yang (Bioresource Technology, 2023)

Arsenic removal and stabilization behavior of schwertmannite@BC (Sch@BC) in contaminated dual media (water/soil): Via sulfate exchange and chemical complexation - Xiao Tan; Jiahao Liu; Meng Liu; Yinjie Zhang; Qi Liu; Guilan Duan; Jun Cui; Aijun Lin (Environmental Pollution, 2023)

Synthesis of zero-valent iron supported with graphite and plastic based carbon from recycling spent lithium ion batteries and its reaction mechanism with 4-chlorophenol in water - Guilan Gao; Zhuoxiang Li; Shuai Chen; Carolina Belver; Donghai Lin; Zixiang Li; Jie Guan; Yaoguang Guo; Jorge Bedia (Journal of Environmental Management, 2023)

Detection by environmental surveillance and genomic characterization of H5N8 highly pathogenic avian influenza virus from a poultry meat market in Beijing, China, 2021–22 - Shujuan Cui; Lin Zou; Yimeng Liu; Jiachen Zhao; Guilan Lu; Weixian Shi; Yang Pan; Xiaomin Peng; Daitao Zhang; Peng Yang; Quanyi Wang (Veterinary Research Communications, 2022)

Sources, Aging, and Management of Coastal Plastics in Shanghai - Shuai Chen; Donghai Lin; Guilan Gao; Jie Guan; Carolina Belver; Jorge Bedia (Water, Air, & Soil Pollution, 2022)

Neurotoxicity of nanoparticles entering the brain via sensory nerve-to-brain pathways: injuries and mechanisms - Yuqing Lin; Chen Hu; Aijie Chen; Xiaoli Feng; Huimin Liang; Suhan Yin; Guilan Zhang; Longquan Shao (Archives of Toxicology, 2020)

Novel Inhalable Ciprofloxacin Dry Powders for Bronchiectasis Therapy: Mannitol–Silk Fibroin Binary Microparticles with High-Payload and Improved Aerosolized Properties - Chunxia Liu; Ling Lin; Zhengwei Huang; Qiaoli Wu; Junhuang Jiang; Li Lv; Xiaoxia Yu; Guilan Quan; Guocheng Li; Chuanbin Wu (AAPS PharmSciTech, 2019)